A new species of Trachygamasus from Poland, a new definition of the genus, and a key to the world species (Parasitiformes: Parasitidae) - Witaliński, Wojciech (Zootaxa, 2017)
A new mite species, Trachygamasus gerdi sp. nov. from the environs of Kraków (southern Poland) is described. A modified diagnosis of Trachygamasus, as well as a key to adults of 10 world species—of 11 known species of the genus—are presented.